Promoting competence motivation via direct explanation : developing a self-efficacious ESL reader / Bromeley Philip - Philip, Bromeley (UPENA, 2006)
This paper attempts to explore the possibility of implementing an explicit strategy instruction to teach academic reading. It provides some interesting review of the literature on the probable benefits of an explicit strategy instruction such as Direct Explanation type of strategy instruction. Besides teaching strategies explicitly, Direct Explanation also incorporates a motivational approach component whereby it emphasises enhancing the learners' level of competence motivation. This in turn helps enhance the learners' level of selfefficacy which enables the learners to a large extent use the strategies effectively in their meaning making process. The increase in the learners' level of self-efficacy beliefs over a period of time was measured using a non-parametric test of Wilcoxon Matched-Pairs Signed-Rank Test (WMPSRT), which denotes a positive result. The learners' performance in recall and comprehension of propositions was also measured for level of significance vis-a-vis that of the control group's, and the results were in favour of the experimental group.